1979
DOI: 10.1002/ar.1091940103
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and the lung. I. Thyroid hormones and glucocorticoids in lung development

Abstract: It has been proposed that thyroid hormones may have a role in the regulation of lung development and the maturation of the surfactant system. The purpose of this study was to examine the effects of exogenous thyroxine (T,) on rat lung development and to investigate possible interactions of this hormone with the glucocorticoids, other hormones implicated in the regulation of lung development.A number of different experimental protocols were utilized: T, was administered to day 17 and 18 rat fetuses from untreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
1

Year Published

1979
1979
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 44 publications
4
28
1
Order By: Relevance
“…Such a regimen might improve/normalize intracellular T 3 concentrations in all tissues (32). It is known that lung maturation is T 3 -dependent (33). A combined T 4 /T 3 treatment could stimulate maturation in both central nervous tissue and peripheral organs such as the lungs.…”
Section: European Journal Of Endocrinology (1998) 139mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a regimen might improve/normalize intracellular T 3 concentrations in all tissues (32). It is known that lung maturation is T 3 -dependent (33). A combined T 4 /T 3 treatment could stimulate maturation in both central nervous tissue and peripheral organs such as the lungs.…”
Section: European Journal Of Endocrinology (1998) 139mentioning
confidence: 99%
“…In addition, T 3 enhances expression of the type I deiodinase gene (27), and T 3 treatment thus could increase endogenous T 3 production. It may, however, be difficult to find an appropriate T 4 /T 3 regimen, because a middle course must be found between a T 3 dose by which maturation is enhanced and morbidity is decreased (33,34), and a T 3 dose that does not increase protein catabolism (35). Treatment with T 3 alone is not advisable, as it will result in lower plasma T 4 concentrations by negative feedback (19), and thus will increase the risk of depletion of cerebral thyroid hormone supply.…”
Section: European Journal Of Endocrinology (1998) 139mentioning
confidence: 99%
“…In a morphological study in the and 21. The increases in glycogen content and fatty acid fetal rat, Hitchcock (7) reported maximal acceleration of lung synthesis were accelerated by dexamethasone and pre-maturation when glucocorticoids and thyroxine were both presvented by T3 and when the hormones were administered ent. Similarly, a synergistic interaction between glucocorticoids together T3 antagonized the stimulatory effects of dexa-and thyroid hormone in stimulating synthesis of phosphatidylmethasone on these parameters.…”
mentioning
confidence: 96%
“…Although the physiologic importance of this T3 neogenesis remains unclear, it is quite possible that T3 exerts the biologic effects of thyroid hormone and, therefore, is responsible for the morphologic changes in fetal and adult type I1 cells which have been described by a number of investigators (for review, see [20][21][22]. It is also possible that T4, rather than acting as a prohormone, has effects of its own, and that in the course of its activity it is metabolized peripherally to other thyronines such as T3 and rT3 These compounds might then simply represent by-products of thyroid hormone action.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Hitchcock and collaborators (20)(21)(22) demonstrated that thyroxine (T4) can accelerate rat lung development and that this acceleration is maximal in the presence of glucocorticoids. Similar findings were noted by Ballard and associates (1, 2) during transplacental stimulation of fetal rabbit lung by an analog of T4 known as DIMIT.…”
mentioning
confidence: 99%